Major microbial points (MMP) in halobacterial contamination of fish curing environments of Andhra coast, India - Prasad, M M; Gopakumar, K; Seenayya, G (Indian Journal of Fisheries, 2011)
The levels of microbial contamination from different environmental sources in theprocess of fish curing in five coastal districts of Andhra Pradesh are reported. Thedescending order of halophilic bacterial contamination is (1) solar salt, dryingground (DG), soil, raised cemented platform (RCP), sea sand (SS) and fish skinsurface (FSS) for red halophilic bacteria; (2) DG, soil, FSS, RCP, solar salt andSS for Halomonas spp. and (3) soil, FSS, solar salt, RCP, DG and SS with respectto slime producing bacteria. A positive correlation was observed with solar saltand SS for red halophiles, soil for Halomonas spp., and DG and solar salt for slimeproducing bacteria. The sources of contamination in relation to cured productshowed that (a) solar salt, RCP and soil for red halophilic bacteria, (b) soil, solarsalt and RCP for Halomonas spp., and (c) DG, soil and solar salt for slime producingbacteria as best sets. An inverse relationship was observed in the occurrence ofred halophiles and slime producing bacteria at different fish curing environs.Occurrence of Halomonas spp., in fish drying grounds is reported for the first time